Theory advances in high-precision two-photon spectroscopy - Haas, Martin (2006)
High-precision two-photon spectroscopy of hydrogen and hydrogenlike systems constitutes an exceptional tool for experimental tests of fundamental theories. In the analysis of these experiments, theory also plays a vital role in the modeling of time-resolved spectra, the calculation of precise transition matrix elements, and the correction of a number of systematic effects. This thesis gives a detailed analysis of the relevant two-photon excitation dynamics, starting from the single-atom response and leading to a Monte Carlo model which can be used for the analysis of atomic beam experiments. Dynamic polarizabilities of relevant S and D states, quantifying the dynamic Stark shift, and transition matrix elements among these states are calculated, taking into account leading-order relativistic, radiative and non-dipole laser-field effects. An important broadening effect of the experimentally observed spectra in the hydrogen 1S2S spectroscopy experiment at the MaxPlanckInstitut für Quantenoptik (MPQ) is identified and quantitatively described, as well as systematic frequency shifts. Corresponding possible improvements to the experimental setup are proposed. By combining the results of repeated MPQ hydrogen 1S2S measurements and other experiments, in collaboration with the MPQ group, separate stringent limits on the possible drift of the magnetic moment of the cesium nucleus and the finestructure constant are deduced.